THU0222 Transient bone marrow oedema and/or transient osteoporosis of the hip are associated with generalised diminution in bone mineral density: role of pre-existing bone fragility ?. (1st June 2001) - Pham, T; Legré, V; Champsaur, P; Chagnaud, C; Lafforgue, P
Abstract : Background: Transient osteoporosis of the hip (TOH) and transient bone marrow oedema of the hip (TBMEH) are uncommon, closely associated and/or similar conditions, whose pathophysiology remains obscure. Several facts suggest that occult microfractures of the femoral head could be the cause of such entities. Objectives: We conducted a prospective assessment of bone status in skeletal sites other than the affected hips to test the hypothesis of pre-existing underlying generalised bone fragility. Methods: 13 consecutive patients with typical signs of TBMEH at MRI were enrolled, with careful exclusion of cases presenting with any sign consistent with either osteonecrosis or stress fractures of the femoral head. Five patients also had radiological signs of TOH. All had prospective bone status assessment including search for risk factors of bone fragility or history of fracture, laboratory tests, spine radiographs and lumbar and femoral neck (of the unaffected hip) by DEXA. Results: There were 8 women (6 pregnant) and 5 men, aged 40 ± 11 years. Four had possible risk factors for osteoporosis, and only 1 had previous insufficiency fracture (rib). Lumbar BMD measurements by DEXA found 1 patient with normal BMD (T-score between 0 and 1SD), 9 patients had a T-score between 1 and 2.5 SD and 2 had T-score less than 2.5 SD. The BMD values were about 15% less than the age/sex matched reference population (mean Z-score 1.4 ± 0.64 SD). BMD values obtained in the unaffected hip in 6 cases confirmed these results. Separate analysis of males/females and pregnant/other patients yielded the same results. Conclusion: Most patients with TBMEH and/or TOH have a generalised decrease in BMD. These results put together with data from the literature suggest that a pre-existing bone fragility is a predisposing factor to TBMEH and/or TOH.